The biography of philosopher as a paradox - Menzhulin, Vadym (Actual Problems of Mind, 2017)
The author argues against the radical compartmentalism, according to which the life and the doctrine of a philosopher should be considered apart. The main idea of the paper is that every thinker reaches the universality by his own way. This is, the author says, the paradox of a philosopher’s biography